THE BEHAVIOR OF THE FAMILY BEFORE THE DIAGNOSIS OF THE CHILD WITH DEAFNESS - Rairam Silva Sobreira, Francisco; Soares Loiola, Michely; José Soares do Nascimento, Maria; Cordeiro de Melo, Keydilanny; Lima de Oliveira, Renan; Rodrigues de Amorim, Jeane (Revista Gênero e Interdisciplinaridade, 2022)
This research concerns the behavior of families regarding the finding that their child is hearing impaired. It reflects on the importance of the family in all aspects to the development of the child, I aim at, which is the first institution in which the child belongs, having the role of caring and educating developing a safe environment. The objective of this work is to identify and analyze the behavior of families regarding the discovery of hearing impairment in a particular member of the child, taking into account reactions, feelings and difficulties. Through a literature review and field research, we sought to know the importance of the family in the development of the deaf child and to identify behaviors regarding the discovery of a deaf child. To support this work, I counted on the contribution of OLIVEIRA (2011) and (SILVA, 2017). It was verified in this study that the diagnosis of hearing impairment causes in parents a great impact and some changes in family dynamics. Shock, suffering and non-acceptance are the main reactions. Feelings of sadness, doubts and uncertainties are constant. However, with the passage of time it is noticed that families accept and overcome such difficulties.